Pemanfaatan bakteri asam laktat dari pekasam tradisional sebagai kultur starter untuk pekasam skala laboratorium : Application of lactic acid bacteria from traditional pekasam as a starter culture for laboratory-scale pekasam - Maherawati, Maherawati; Tridayanti, Devi; Hartanti, Lucky; Mayasari, Eva (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Pekasam is one of the traditional fish-based foods made by fermentation. Traditionally, pekasam is made by spontaneous fermentation, so it has inconsistent characteristics. This study aims to determine lactic acid bacteria (LAB) isolates from traditional pekasam as starter cultures for laboratory-scale pekasam fermentation. Traditional pekasam samples were obtained from three pekasam artisans from Sambas Regency, West Kalimantan (SB1, SB2, and SB3). The isolation of LAB from the three pekasam samples resulted in the acquisition of 34 isolates. Isolates have a round shape, flat edges, and a convex surface. Colonies found consisted of 32 milky white colonies and 2 yellowish white colonies. The isolates were gram-positive, with 31 bacillus-shaped cells and 3 coccus-shaped cells. Six LAB isolates selected from proteolytic and hemolytic testing were SB1.1, SB1.5, SB2.4, SB3.1, SB3.2, and SB3.8. Based on the proteolytic index value, three isolates (SB1.1, SB1.5, and SB2.4) were selected as starter cultures in the manufacture of laboratory-scale pekasam. The results indicated that the addition of starter culture in making pekasam had a significant effect on the ash, protein, fat, and fiber content of pekasam produced but had no effect on the moisture content of pekasam. The ash content of laboratory-scale pekasam was 7.12-7.32%, protein 12.68-13.07%, fat 5.43-8.80%, carbohydrate 6.97-10.45%, fiber 7.58-7.90%, energy 143.85-162.18 cal/100 g, and water 55.87-56.4%.